Exploring predictors of walking ability among community-dwelling older adults. (April 2013) - Satchidanand, Nikhil; Fox, Chester; Brunton, Kimberly; Freudenheim, Jo; Hassett, James; Naughton, Bruce; Cherr, Gregory S
Aims: The objective of this analysis was to examine the association between complex multidimensional factors and walking ability among older adults.Methods: In total, 200 patients completed literature-validated questionnaires to assess depressive symptoms, psychosocial stress and chronic pain. Previous medical diagnoses and medication usage were also recorded. BMI was calculated and walking ability was estimated using the Six-Minute Walk Test. Multiple regression was performed to ascertain the contribution of the predictor variables on distance walked.Results: The overall model accounted for 61.2% of the variance in walking ability. Age, number of medications used and number of comorbid conditions were predictive of distance walked along with chronic pain, depressive symptoms and BMI (p < 0.05).Conclusion: These findings indicate that walking ability is influenced by complex multidimensional factors, many of which can be managed. Comprehensive intervention should focus on ameliorating depressive symptoms and chronic pain, and preventing excess weight gain in older adults.